Crystal structure of 3-(3-bromophenyl)-1′,3′-dimethyl-2′H,3H,4H-spiro[furo[3, 2-c]chromene-2,5′-pyrimidine]-2′,4,4′,6′(1′H,3′H) tetraone, C22H15BrN2O6 - Jiang Dong-Li; Fan Lian-Lian; Yin Peng; Liang Di; Li Rui (Zeitschrift für Kristallographie - New Crystal Structures)
C22H15BrN2O6, monoclinic, P21/c (No. 14), a = 5.1760 (5) Å, b = 17.5652(19) Å, c = 21.734(2) Å, β = 94.690(3) °, Z = 4, V = 1969.3(3) Å3, Rgt(F) = 0.0569, wRref(F2) = 0.1206, T = 170 K.